Pola Perubahan Ziarah Makam sebagai Arena Sosial - Arifin, Suherman (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2020)
The changing pattern of the grave pilgrimage as a social arena has undergone various changes. The tradition of pilgrimage to the tombs has been going on hundreds of years ago and in Islam. This study aims to determine how the pattern of changes in the grave expedition as a social arena. This article discusses habitus, arenas, social capital and practices that occur in society. Qualitative data with case studies are the approach used in the analysis. The data collection technique was carried out in three different ways, including in-depth interviews, discussions with the Nazirite tombs and document studies. Secondary sources were obtained through the old Banten museum, regional libraries, Nadziran documents, news on the pilgrimage site announcement boards, previous research reports, related papers, journal articles, visualization documents in the form of photographs others. The data analysis technique starts with data reduction, data presentation and concluding. This research resulted in several findings including grave pilgrimage as an arena for a family gathering, an arena for healing mental illnesses, an arena for work images, an arena for spiritual healing, an arena for hereditary ritual habitus, and a hall for symbolic power.